"A mass of anomalies": Land, Law, and Sovereignty in an Indian Company Town. (27th March 2018) - Raianu, Mircea
Abstract: This article examines the emergence of Jamshedpur, site of India's first steel plant and privately governed company town, as part of an unprecedented large-scale extraction of mineral resources at the turn of the twentieth century for the purpose of industrial development. It traces the protracted acquisition of land and dispossession of mainly adivasi (tribal) cultivators by the Tata Iron and Steel Company (TISCO) from ca. 1900 to 1930. The company pursued a distinct strategy of obtaining short-term leases from princely states and zamindars (landowners), while simultaneously appealing to the legal apparatus of the colonial state to secure absolute tenurial rights. The uneven application of laws such as the Land Acquisition Act (1894) and the Chota Nagpur Tenancy Act (1908) allowed TISCO to become a quasi-sovereign power in eastern India, simultaneously acting as employer, landlord, and municipal government. Jamshedpur's continually anomalous legal status underlies the persistence of multiple, fragmented, and competing sovereignties in India, even as an ostensibly unified national economic state space emerged by the time of independence in 1947. More broadly, it suggests that the contours of the relationship between states and corporations, particularly in a postcolonial context, are determined both by preexisting political geographies and contingent legal struggles.